iTBS over the left hV6A enhances PPC-PPC functional connectivity during reaching tasks: an EEG study - Chen, Jing; Ding, Qian; Li, Ya-wen; Huang, Yu-hong; Yao, Shan-tong; Guo, Ri-yu; Wang, Long-ping; Wei, Xin-hua; Lan, Yue; Xu, Guang-qing (Frontiers in neuroscience, 2025)
The functional connectivity of the posterior parietal cortex-primary motor cortex (PPC-M1) is involved in goal-directed reaching actions and integrating visuomotor transformation. Human area V6A (hV6A), located in the medial PPC, is a critical node of the dorsomedial system that is involved in targeting during reaching movements. Here, we used Electroencephalography (EEG) to investigate functional connectivity and network efficiency during right-hand reaching tasks after inducing left hV6A activity with intermittent theta burst stimulation (iTBS). Based on individualized MRI neural navigation, 23 healthy subjects were randomly accepted into either real left hV6A or sham iTBS on 2 days. Resting-state and goal-directed reaching task EEG were recorded at baseline and immediately after iTBS to assess the effects of iTBS on functional connectivity. Alongside the reaching task, an additional Stroop test was conducted to assess each participant's degree of attention. In the alpha band, medial posterior parietal cortical interhemispheric functional connectivity significantly increased during right-hand reaching tasks after hV6A iTBS ( 0.008) but not after sham iTBS ( 0.726). Alpha and beta bands small-worldness of right-hand reaching tasks significantly increased ( 0.001 and 0.013, respectively) but not after sham iTBS ( 0.915 and 0.511, respectively). Functional connectivity of the bilateral PPC and functional network efficiency increased after iTBS of the left hV6A during right-hand reaching tasks. These findings indicate that the left hV6A should be a potential target for iTBS modulation to improve the orienting movement function in space.